Kontribusi Komunikasi Persuasif Dan Pengalaman Organisasi Mahasiswa Jurusan PLS FIP UNP Terhadap Pengelolaan Program Pendidikan Nonformal - Azizah, Zahratul; Aliasar, Aliasar; Darmansyah, Darmansyah (Konselor, 2015)
This research was dealing with the management of nonformal education program conducted by students on school education beyond the PPL PLS at Kecamatan Koto Tangah indicated in good enough result. This study attempts to get an overview of the ability to persuasive communication and experience of the organization, then to reveal of the contribution between the variables. The research was quantitative research by applying a technique of correlational, where the population of this study was all students ofÂ  PLS FIP UNP who carried out the PPL PLS and haveÂ  experiences of the organization. The results of this research showed that: the picture of persuasive communication ability and experience organisations of student were good; persuasive communication contribute positively and significant to management of nonformal education program; experience of the organization contribute positively but less significant on the management of nonformal education program; persuasive communication and experience of the organization jointly positive contributed and significantly to management of nonformal education program.